k2-3≥0

Add 3 to both sides of the inequality.

k2≥3

Take the square root of both sides of the inequality to eliminate the exponent on the left side.

k≥±3

First, use the positive value of the ± to find the first solution.

k≥3

Next, use the negative value of the ± to find the second solution. Since this is an inequality, flip the direction of the inequality sign on the – portion of the solution.

k≤-3

The complete solution is the result of both the positive and negative portions of the solution.

k≥3 or k≤-3

k≥3 or k≤-3

The result can be shown in multiple forms.

Inequality Form:

k≥3 or k≤-3

Interval Notation:

(-∞,-3]∪[3,∞)

=\sqrt(3)","color":0,"isGrey":false,"dashed":false,"holes":[]},{"ascii":"k

Simplify k^2-3>=0